(untitled) (VITEK : Bidang Kedokteran Hewan, 2023)
Feline calicivirus (FCV) is a highly contagious and pathogenic viral disease with widespread transmission in the cat population. A cat named Sapi with black and white hair color, weighs 1.94 Kg, male sex, and is 9 months old. On December 1, 2022, the Sapi’s cat came to the clinic in a weak and unsteady condition, had not defecated, still wanted to drink, had normal urination, had eye discharge. Investigations with the FCV test kit showed positive results for the FCV virus. Hematological examination showed that Sapi’s cat had leukocytosis, granulocytosis and lymphocytosis. Sapi were given normal saline and neurobion drip intravenously, injection of Cefotaxime 0.2 ml q12h antibiotics, Glucortin injections 0.25 ml q24h, Vitol injections 1 ml q24h, Calcidex injections 0.2 ml q12h, Biodin injections 0.2 ml , oral therapy of Fibumin 1 capsule q12h, Transfer factor 1 capsule q12h, Oxyfresh water additive 0.5 ml q12h, serum eye drops q12h, cendo hyalub q12h and Bio ion spray for ear scabs. Keywords: Feline Calicivirus, Cats, FCV Test Kit